Exploring corrections in America - Whitehead, John T. (LexisNexis, 2008)
Understanding corrections -- The history of American corrections -- Corrections and the courts -- Jails -- Community corrections -- Dimensions of community justice -- Prisoners and prison life -- Women offenders and correctional workers -- Juvenile corrections -- Special populations -- Correctional officers -- Correctional counselors and other treatment professional -- Issues in correctional administration and management -- The death penalty in America -- The evolution of corrections : what does the future hold?